2017
DOI: 10.1007/s00203-017-1347-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land use on bacterial and archaeal diversity and community structures in three natural ecosystems and one agricultural soil

Abstract: Studying shifts in microbial communities under different land use can help in determining the impact of land use on microbial diversity. In this study, we analyzed four different land-use types to determine their bacterial and archaeal diversity and abundance. Three natural ecosystems, that is, wetland (WL), grassland (GL), and forest (FR) soils, and one agricultural soil, that is, tea plantation (TP) soil, were investigated to determine how land use shapes bacterial and archaeal diversity. For this purpose, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 47 publications
4
23
0
Order By: Relevance
“…This study explored soil physicochemical properties and bacterial communities from different sites under different green space types in Beijing: PARK, RESID, ATTACH and STREET. It is well known that soil physicochemical properties can be affected greatly by land use types in agriculture and forests [9,29,30]. Similar findings were found in this study: green space types play critical roles in the maintenance of soil physicochemical properties especially in soil total nitrogen, pH value, soil organic matter and soil moisture content by affecting management practices.…”
Section: Discussionsupporting
confidence: 88%
“…This study explored soil physicochemical properties and bacterial communities from different sites under different green space types in Beijing: PARK, RESID, ATTACH and STREET. It is well known that soil physicochemical properties can be affected greatly by land use types in agriculture and forests [9,29,30]. Similar findings were found in this study: green space types play critical roles in the maintenance of soil physicochemical properties especially in soil total nitrogen, pH value, soil organic matter and soil moisture content by affecting management practices.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, there were significant correlations between the bacterial 16S rDNA gene abundance and soil pH, TN content, and SOC content, which further indicated that these soil properties might be the key factors affecting the bacterial abundance in this study. Bacteria played important roles in soil nutrient cycles [8,10,13], and higher bacterial 16S rDNA gene abundance implied that there might be more bacteria participating in soil N, P, and K cycling and supplying more available N, P, and K resources for rice plants and indirectly influencing the rice production.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed no significant difference in the soil nutrients (N, P, and K).Only soil pH significantly decreased in the 30-year-old tea plantation when compared with the bulk soil and the two-year-old tea field, which resulted in lowering the abundance of rhizospheric microbiota, such as Actinobacteria , Cyanobacteria , Chloroflexi , and WD272 [ 35 ], and showed direct association with Nitrospirae , Gemmatimonadetes , and Acidobacteria. On the other hand, Proteobacteria and Bacteroidetes were the most dominant bacterial group present in the 30-year-old tea plantation [ 43 , 44 ], which may be because these bacterial taxa prefer to live in a root vicinity with nutrient deficiency, high soil moisture (MOS), and lower pH. Previous studies on bacterial communities have clearly shown that nutrient deficiency did not significantly impact the soil microbiota, however soil pH was proven to be the most influential factor in shaping the soil microbiota [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%